1992
DOI: 10.1136/bmj.305.6862.1119
|View full text |Cite
|
Sign up to set email alerts
|

Venous leg ulcers: a prognostic index to predict time to healing.

Abstract: Objective-To evaluate the prognostic factors in uncomplicated venous leg ulcer healing.Design-Randomised parallel group controlled trial with subjects stratified by initial ulcer diameter and four months' maximum duration offollow up.Setting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(123 citation statements)
references
References 11 publications
(2 reference statements)
9
108
1
5
Order By: Relevance
“…11 With the demographic changes that have occurred in the present day to population of the developed countries, 11 as well as in Brazil, geriatric diseases are expected to be more frequent in the medical routine, and among them leg ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…11 With the demographic changes that have occurred in the present day to population of the developed countries, 11 as well as in Brazil, geriatric diseases are expected to be more frequent in the medical routine, and among them leg ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Increased age was associated with slower healing rates in one study, 47 therefore age would be considered as a potential factor influencing healing. Only patients of 18 years and over were entered into the trial.…”
Section: Date Of Birthmentioning
confidence: 99%
“…9,10,47 The majority of patients in this trial (82%; 316/387) had a reference ulcer with an area of ≤ 10 cm 2 . A few ulcers were very large, ranging up to 255 cm 2 (almost 16 by 16 cm square) ( Table 6).…”
Section: Area Of Reference Ulcermentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Table 1, several studies have shown no association between any specific bacterial species and healing outcomes. 16,[29][30][31][32][33] Among studies that show associations, there are conflicting conclusions on the relevance of many of the commonly isolated species, such as Staphylococcus aureus and Pseudomonas species, as well as anaerobes ( Table 2). Most studies of S. aureus show no association with healing delay or increased ulcer size.…”
Section: Presence Of Pathogenic Organismsmentioning
confidence: 99%